Leaf formononetin content of Trifolium subterraneum increases in response to waterlogging but its proportion of total isoflavones is little changed - Enkhbat, Gereltsetseg; Foster, Kevin J.; Nichols, Phillip G. H.; Erskine, William; Inukai, Yoshiaki; Ryan, Megan H. (Functional Plant Biology, 2023)
The isoflavone formononetin (F) impacts livestock fertility and cultivars of the pasture legume Trifolium subterraneum L. (subclover) have been selected for F levels ≤0.2% of leaf dry weight. However, the impact of waterlogging (WL) on isoflavones is little studied. We investigated the response of isoflavones, biochanin A (BA), genistein (G) and F, to WL for: (1) Yarloop (high F) and eight low F cultivars each from subspecies subterraneum, brachycalycinum and yanninicum (Experiment 1); and (2) four cultivars and 12 ecotypes of ssp. yanninicum (Experiment 2). WL impacted F: estimated means increased from 0.19% (control) to 0.31% (WL) in Experiment 1 and from 0.61% to 0.97% in Experiment 2. Isoflavones under WL were highly heritable, particularly F (H2 = 95%). The proportions of BA, G and F were little changed by WL, with strong positive correlations between free-drained and waterlogged treatments. Isoflavone contents were not related to WL tolerance, as assessed by shoot relative growth rate. In conclusion, isoflavones varied among genotypes and increased with WL, but the proportion of individual isoflavones in each genotype was stable. High F under WL was unrelated with genotype tolerance to WL. Instead, it was a consequence of inherently high F for that particular genotype.